To answer this question we will use the quotient rule for derivatives:
![((h(x))/(g(x)))^(\prime)=(h^(\prime)(x)g(x)-h(x)g^(\prime)(x))/(g(x)^2)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/uka8u089lrovfc45ej23uqtcnywt35plw1.png)
We know that:
![\begin{gathered} (\sqrt[]{x})^(\prime)=\frac{1}{2\sqrt[]{x}}, \\ (5x-6)^(\prime)=5. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a9bde2h1ju74sioe60omcd39yqz1zw91xv.png)
Then:
![f^(\prime)(x)=\frac{\frac{1}{2\sqrt[]{x}}\cdot(5x-6)-\sqrt[]{x}\cdot5}{(5x-6)^2}\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/1vs9pcy9xllufwya8dbr69m8uf7zmt3r29.png)
Therefore, the slope of the tangent line to the graph of f(x) at (1,f(1)) is:
![f^(\prime)(1)=\frac{\frac{1}{2\sqrt[]{1}}(5\cdot1-6)-\sqrt[]{1}\cdot5}{(5\cdot1-6)^2}\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/pwp12b2vduz8eyhbiolxveo1eej45et9ts.png)
Simplifying the above result we get:
![\begin{gathered} f^(\prime)(1)=((1)/(2)(5-6)-5)/((5-6)^2) \\ =((1)/(2)(-1)-5)/((-1)^2)=(-(1)/(2)-5)/(1)=-(11)/(2)\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/za5srnucg3yyw6yxderyi7fr6538av5afh.png)
Now, we will use the following slope-point formula for the equation of a line:
![y-y_1=m(x-x_1)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/50rdws8olj8e9mrccwea6tp7o8rrt3xm71.png)
Therefore the slope of the tangent line to the graph of f(x) at (1,f(1)) is:
![y-f(1)=-(11)/(2)(x-1)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/zrrwtv4dc9ovms1oyolqmsogakzurty0te.png)
Now, we know that:
![f(1)=\frac{\sqrt[]{1}}{5\cdot1-6}=(1)/(5-6)=(1)/(-1)=-1.](https://img.qammunity.org/2023/formulas/mathematics/college/pbetink6seywv2cmkdch96yz7u0m3wvaez.png)
Therefore:
![\begin{gathered} y-(-1)=-(11)/(2)(x-1), \\ y+1=-(11)/(2)x+(11)/(2)\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7co206txe2c7ad41hyikjtue1on801ogrr.png)
Subtracting 1 from the above equation we get:
![\begin{gathered} y+1-1=-(11)/(2)x+(11)/(2)-1, \\ y=-(11)/(2)x+(9)/(2)\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yq97ggudvpj762p1flaen4ube8yw6feuar.png)
Answer:
![y=-(11)/(2)x+(9)/(2)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/kitnhzyjt1lxfzgxuej5ry60x6do4x75zn.png)